Romeo and Juliet – play about love and death - Andrejevic, Ana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In the play Romeo and Juliet, which has become the synonym for the love tragedy, death is represented as the ultimate, all-consuming, and almost nihilistic power that cannot be conquered even by the most pure and passionate love. But, its devastating effect is reduced by the strong, transcendent, and the idealistic vision of love of the two young creatures who became immortal as the materialistic golden monuments, due to the power of the eternal art and the word of Shakespeare. Presenting it in the traditional frame of the Dance of Death and memento mori iconography, Shakespeare is showing us the different aspects of the Renaissance thought of death. The older generation sees it as the natural progression of life that cannot and must not stop everyday activities, but the younger hopes to find in death the salvation and escape from the insupportable and pragmatic world. Although there are religiously guided thoughts about life after death in the play, secular statements about death as a flight from the unbearable reality and the cure for the impossible love are more present. Even suicide is not conventionally represented as the sinful and devilish enterprise that must be condemned, but as the sacrifice and radical attempt to protect and preserve love. Shakespeare makes his lovers the owners of death, despite the rigid patriarchal effort to control both life and its opposite force. Love of Romeo and Juliet thus becomes victorious in death.
Keywords: Memento mori; "Dance of Death"; tragedy; death; love; Romeo and Juliet; William Shakespeare